Transcultural Film Adaptations as Cross-Cultural Dialogue - Boginskaya, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2023)
This article explores a transcultural ﬁlm adaptation, offerinf new avenues for discussing cross-cultural dialog. The article analyzes the transcultural adaptation of Doctor Zhivago, written by Boris Pasternak. The book was adapted in 1965 by British director David Lean, who cooperated with one of the largest American ﬁlm studios, Metro-Goldwyn-Mayer. This work considers the changing meaning of the text, which enters a new national culture, and explores how Pasternak’s novel was changed to ﬁt the new audience. Lean’s adaptation of Doctor Zhivago is analyzed as a dialogue of different cultures, which involve the “Hollywoodization” of Russian literature. The author emphasizes the intertextual and cultural dialogism of Boris Pasternak’s novel Doctor Zhivago and David Lean’s 1965 ﬁlm adaptation. The ﬁlm adaptation inserts the novel into much broader dialogic relations, for example, with movies of a speciﬁc era, their cinematic technics, and ideologies.